ANALISIS INTERSEKSIONAL KECANTIKAN PEREMPUAN INDONESIA MELALUI DISKRIMINASI WARNA KULIT TIKTOK - Nikita; Ananda Dias Pribadi (Universitas 17 Agustus 1945 Surabaya, 2026)
Beauty standards for women in Indonesia continue to be shaped by skin color hierarchies that position fair skin as an ideal symbol of attractiveness, modernity, and social value. These standards are not merely the result of individual aesthetic preferences, but are deeply rooted in colonial legacies, social class stratification, and patriarchal culture that are continuously reproduced through mass media and digital platforms. This condition is clearly reflected in the practice of colorism within digital spaces, particularly on social media. One prominent example is the case of TikTok influencer Ratu Namira, who became the target of derogatory public comments focusing on her skin tone rather than the quality or substance of her content. This study aims to analyze how skin color discrimination against women is constructed,Volume 5 No. 1 Januari 2026https://jurnal.untag-sby.ac.id/index.php/sintesaE – ISSN 2986-3759JURNAL ILMIAH KAJIAN KOMUNIKASI175normalized, and intensified in digital public spaces through an intersectional perspective. This research employs a qualitative approach using digital discourse analysis and visual analysis of public commentsrepresentations of women’s bodies on TikTok. The analytical framework is grounded in third-wave feminism, the concept of the male gaze, and algorithmic bias theory in order to examine the intersections of gender, skin color, social class, and digital technology. The findings reveal that the harassment directed at Ratu Namira cannot be understood as neutral aesthetic judgment, but rather as a form of symbolic violence reflecting the convergence of colonial history, patriarchal norms, and class-based hierarchies. Furthermore, TikTok’s algorithm plays a significant role in amplifying discriminatory discourse by prioritizing content and comments that generate high levels of engagement. Consequently, colorism against dark-skinned women on social media constitutes a form of structural discrimination that operates simultaneously across social, cultural, and digital domains, shaping women’s representation, lived experiences, and social positioning within online spaces.Keywords: Colorism, Beauty Standards, Intersectionality, Women, TikTok